Pengembangan KIT Praktikum Spektrofotometer Sederhana Deteksi Pencampuran Minyak Kelapa Sawit Berbasis STEM-PjBL untuk Meningkatkan Keterampilan Proses Sains Mahasiswa - Dea Safitri; Nurhamidah; Rendy W. Wardhana; Euis Nursa'adah (PendIPA Journal of Science Education, 2026)
The goal of this study was to develop and evaluate the feasibility and preliminary effectiveness of a STEM-PjBL-based simple spectrophotometer practicum kit for detecting palm oil adulteration with used cooking oil and improving students’ science process skills. The study employed a Research and Development method using the ADDIE model and a one-group pretest-posttest design. The product consisted of a practicum kit, a guidebook containing student worksheets, and a web application. The implementation involved 24 Chemistry Education students at the University of Bengkulu. Feasibility was examined through expert validation, Aiken’s V, and a limited trial, whereas effectiveness was evaluated using normalized gain, the Shapiro-Wilk test, a paired samples t-test, and paired Cohen’s d. Expert validation yielded a feasibility score of 85.23% (highly feasible), Aiken’s V values of 0.83–1.00, and a limited-trial score of 94.64%. The kit readings showed a very strong relationship with the UV-Vis reference data at 338 nm (R²=0.9980; RMSE=0.0279). The mean science process skills score increased from 14.00 to 30.25, with a normalized gain of 0.74. Difference scores were normally distributed (p=0.138), and the paired t-test indicated a significant improvement, t (24) =15.901, p<0.001, with a very large effect size (d=3.246). The kit was highly feasible and demonstrated preliminary effectiveness for instrumental analytical chemistry practice; however, the absence of a control group limits causal generalization.